New Information on Rabbi Meir ibn Gabbai and His Autograph Manuscripts - Matanky, Eugene D. (Zutot, 2026)
This article examines select responsa literature and manuscripts to expand our knowledge concerning Meir ibn Gabbai (1480/1-after 1546) and his family. It begins by detailing a responsum by Joseph b. Moses of Tarani (1568-1639) concerning an unmentioned son, Ezekiel ibn Gabbai, which also records the names of Ibn Gabbai’s wife and daughter-in-law. This responsum is further contextualized through recourse to other contemporary responsa that mention other individuals named. In so doing, this article suggests that Ibn Gabbai had a family home in Manisa, Turkey. Next, this article identifies three manuscripts as containing Ibn Gabbai’s autograph through the employment of paleographical, codicological, and philological tools. One of these manuscripts offers us his latest known date and place, Edirne, Turkey in 1546.